Soccer-Specific Stadiums and Attendance in Major League Soccer: Investigating the Novelty Effect - Adam Love; Andreas N. Kavazis; Alan Morse; Kurt C. Mayer Jr. (Journal of Applied Sports Management, 2013)
Major League Soccer (MLS) officials have focused on the construction of soccer-specific stadiums as a key aspect of the league’s development strategy. Research in numerous professional sport contexts has found that teams tend to experience an increase in attendance after moving into new stadiums. Researchers have termed this phenomenon the novelty effect. Given MLS’s longtime emphasis on constructing soccer-specific stadiums, the purpose of the current study was to examine the extent to which a novelty effect exists in MLS. Results of a repeated measures t test indicated that clubs experienced an increase in attendance during their first season in a soccer-specific stadium, and this novelty effect appears to persist to a significant extent for at least 3 years. However, the relatively young age of the league, the success of a club such as Seattle Sounders FC playing in a multipurpose venue, and the costs associated with stadium construction present important issues for further research and consideration.
Keywords: Attendance; stadiums; soccer; Major League Soccer; novelty effect